PROPOSED DIGITAL MARKETING STRATEGY FOR BYKOSHKOSH WEBSITE (The Indonesian Journal of Business Administration, 2019)
Bykoshkosh is an online shop focusing on fashion industry that offers several clothing products for daily basis. In the current development of technology especially the uses of internet, people's demand and interest for online shopping are high. Not merely online platforms, but social media platform such as Instagram is also getting popular among Indonesian as a shopping online platform.At this stage, Bykoshkosh wants to increase sales by utilizing Bykoshkosh website (www.Bykoshkosh.com). Bykoshkosh wants to increase demand to increase customer traffic for Bykoshkosh website. In this research, Bykoshkosh seeks the way to improve sales and marketing through Bykoshkosh official website by using quantitative descriptive method, interviews, questionnaire, several theories and benchmarking to Bykoshkosh competitors. The author uses AIDAS theory, Marketing Mix 7P, and Digital Marketing.However, the data from questionnaire showed there are still many customers who do not now the existence of Bykoshkosh official website caused by the lack of promotion through social media, payment method choices, and information. Furthermore, this research will explain more about the digital marketing which was used as a media promotion for Bykoshkosh to improve sales. There are several result that can be implemented in Bykoshkosh company. One of which is develop the digital marketing strategy especially in social media needs to promote Bykoshkosh website. Optimization Bykoshkosh website to increase sales and visitor through Bykoshkosh website. Bykoshkosh also create activity plan each month to develop the service and quality regarding to our product. Keywords: Digital Marketing, Online Shopping, Bykoshkosh, Website.